2020
DOI: 10.1002/nau.24294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of levator hiatal overdistension after vacuum and forceps deliveries

Abstract: Introduction: Levator ani avulsion rates after assisted vaginal delivery have been reported in the literature. However, there are no definitive data regarding the association between overdistention and assisted vaginal delivery. Therefore, our aim is to report overdistention rates after assisted vaginal delivery with a postpartum ultrasound examination. Materials and Methods:This multicenter study involved a retrospective analysis of data from primiparous women (n = 602) who had previously been recruited at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Clinical assessment of the pelvic floor muscles is subjective and poorly reproducible 3 . Over the past few years, many studies have demonstrated that transperineal ultrasound (TPU) is a reliable and reproducible instrument for the assessment of pelvic floor muscle integrity and function, both in static and dynamic conditions 4‐9 . Proper pelvic floor contraction normally leads to a reduction in levator hiatal dimensions 10 whereas increased levator hiatus dimensions under Valsalva maneuver indicates pelvic floor distensibility and proper LAM relaxation 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical assessment of the pelvic floor muscles is subjective and poorly reproducible 3 . Over the past few years, many studies have demonstrated that transperineal ultrasound (TPU) is a reliable and reproducible instrument for the assessment of pelvic floor muscle integrity and function, both in static and dynamic conditions 4‐9 . Proper pelvic floor contraction normally leads to a reduction in levator hiatal dimensions 10 whereas increased levator hiatus dimensions under Valsalva maneuver indicates pelvic floor distensibility and proper LAM relaxation 11 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Over the past few years, many studies have demonstrated that transperineal ultrasound (TPU) is a reliable and reproducible instrument for the assessment of pelvic floor muscle integrity and function, both in static and dynamic conditions. [4][5][6][7][8][9] Proper pelvic floor contraction normally leads to a reduction in levator hiatal dimensions 10 whereas increased levator hiatus dimensions under Valsalva maneuver indicates pelvic floor distensibility and proper LAM relaxation. 11 Some women are unable to relax their pelvic floor under Valsalva, thus leading to a reduction in the anteroposterior diameter (APD) of the levator hiatus during Valsalva maneuver.…”
Section: Introductionmentioning
confidence: 99%